Residents’ perceptions on impacts of hosting the “Guimarães 2012 European Capital of Culture”: comparisons of the pre-and post-2012 ECOC - Remoaldo, Paula (2015)
Residents tend to have high expectations about the benefits of hosting a mega‐event. So, it was not surprising that the nomination of Guimarães, Portugal, as the 2012 European Capital of Culture (2012 ECOC) had raised great expectations in the local community towards its socio‐economic and cultural benefits. The present research was designed to examine the Guimarães residents’ perceptions on the impacts of hosting the 2012 ECOC approached in two different time schedules, the pre‐ and the post‐event, trying to capture the evolution of the residents` evaluation of its impacts. For getting the data, two surveys were applied to Guimarães` residents, one in the pre‐event phase, in 2011, and another in the post‐event phase, in 2013. This approach is uncommonly applied to Portugal data and it is even the first time it was done to a Portuguese European Capital of Culture. After a factor analysis, the results of t‐tests indicate that there were significant differences (p<0.05) between the samples from the pre‐ and post‐2012 ECOC on two positive impact factors (Community’ benefits and Residents’ benefits) and one negative impact factor (Economic, social and environmental costs). Respondents also showed a negative perception of the impacts in all dimensions, except Changes in habits of Guimarães residents.